2021
DOI: 10.5334/aogh.3049
|View full text |Cite
|
Sign up to set email alerts
|

Using School-Based Health Programs to Prevent Human Trafficking: The Mount Sinai Experience

Abstract: This article describes how school-based health centers can serve as human trafficking prevention sites.Setting: School-based health centers are available to all students attending a school and are often located in schools whose students have risk factors associated with human trafficking: those with a history of running away from home; unstable housing or homelessness; a history of childhood maltreatment or substance use; LGBTQidentification; physical or developmental disabilities, including students who have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Cus et al (2021) argued from a different perspective that faculty strength and the managerial philosophy adopted by university management positively affect student satisfaction. Hilda et al (2021) found out that security, value for money, and courtesy of university staff define student satisfaction while Diaz et al (2021) discovered that convenience of location, prompt service, safety, and security, and friendliness of employees of the university are critically important. Buabeng-Andoh (2021) specified that employee attitude is likely to influence students' satisfaction.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Cus et al (2021) argued from a different perspective that faculty strength and the managerial philosophy adopted by university management positively affect student satisfaction. Hilda et al (2021) found out that security, value for money, and courtesy of university staff define student satisfaction while Diaz et al (2021) discovered that convenience of location, prompt service, safety, and security, and friendliness of employees of the university are critically important. Buabeng-Andoh (2021) specified that employee attitude is likely to influence students' satisfaction.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%